The impact of technological and non-technological innovations on firm growth - Jyrki Ali-Yrkkö; Olli Martikainen (The Research Institute of the Finnish Economy (ETLA), 2008)
This study investigates the relationship between innovations and firm growth, based on the data of Finnish firms operating in the software industry. We find that in terms of turnover and employment, firms with only technological innovations do not grow more rapidly than other firms. However, firm growth is positively associated with the combination of technological and non-technological innovations.
Keywords: O3; O33; L2; 330; Innovation; technological; non-technological; R&D; firm; development; employment; growth; Finland; Innovation; Betriebliche Forschung; Unternehmensentwicklung; Beschäftigung; Softwareindustrie; Finnland